2017
DOI: 10.17221/206/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Finger millet bioactive compounds, bioaccessibility, and potential health effects - a review

Abstract: Udeh H.O., Duodu K.G., Jideani A.I.O. (2017): Finger millet bioactive compounds, bioaccessibility, and potential health effects -a review. Czech J. Food Sci., 35: 7-17.Finger millet is among minor cereal grains that are underutilised. However, over the years, research interest in the millet has increased owing to its abundance of bioactive compounds. These compounds which include, among others, ferulic acid-rich arabinoxylans or feraxans, ferulic acid, caffeic acid, and quercetin have been associated with cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…Seed germination of finger millet can increase the bioavailability of iron from 0.75 to 1.25 mg/100 g and is a potential alternative to mitigate anemia (Tatala et al, 2007). The preprocessing of grains can drastically reduce the impact of antinutrients and can improve iron bioavailability and bioactive compounds, which are confirmed by several scientific studies (Tatala et al, 2007;Hithamani and Srinivasan, 2014;Udeh et al, 2017) (Tables 5 and 6). Singh et al (2018) showed that traditional knowledge practiced by farmers to roast finger millet decreases phytochemical composition, moisture, protein, and antioxidant action, but increases fat, ash, and fiber and improves the bioavailability of iron and calcium.…”
Section: Bioavailability and Improvement In Molecular Genetics Fingermentioning
confidence: 58%
See 2 more Smart Citations
“…Seed germination of finger millet can increase the bioavailability of iron from 0.75 to 1.25 mg/100 g and is a potential alternative to mitigate anemia (Tatala et al, 2007). The preprocessing of grains can drastically reduce the impact of antinutrients and can improve iron bioavailability and bioactive compounds, which are confirmed by several scientific studies (Tatala et al, 2007;Hithamani and Srinivasan, 2014;Udeh et al, 2017) (Tables 5 and 6). Singh et al (2018) showed that traditional knowledge practiced by farmers to roast finger millet decreases phytochemical composition, moisture, protein, and antioxidant action, but increases fat, ash, and fiber and improves the bioavailability of iron and calcium.…”
Section: Bioavailability and Improvement In Molecular Genetics Fingermentioning
confidence: 58%
“…Finger millet is relatively popular in India and many countries in Africa because of its resilience and nutrientdense grain profile. It has been promoted in Africa to reduce anemic incidence in children (Tripathi and Patel, 2010;Udeh et al, 2017). The nutraceutical importance of finger millet lies in its high content of calcium (0.38%), protein (6-13%), dietary fiber (10-18%), carbohydrate (65-75%), and minerals (2.5-3.5%).…”
Section: Bioavailability and Improvement In Molecular Genetics Fingermentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols are regarded as major antioxidants that conduct activities which help to maintain the body immune system. Polyphenols occur naturally in a wide range of food products including FM grains (Siwela et al, 2007;Devi et al, 2014;Udeh et al, 2017). Tannins in the outer layer of the grain, serves as a physical barrier to fungal invasion (Devi et al, 2014) and plays an important role in the biological function of plants and humans.…”
Section: Nutritional Antioxidant Properties and Potential Health Benmentioning
confidence: 99%
“…Millets are typically rich in phenolic compounds (Chandrasekara & Shahidi, 2011). As in most cereal grains, sorghum and millets contain major polyphenol groups such as phenolic acids and flavonoids (Awika & Rooney, 2004;Dykes & Rooney, 2006;Udeh, Duodu, & Jideani, 2017). Furthermore, several studies have reported that bran of sorghum and millets possess the higher phenolic acids as compared to the seed coat of dicotyledonous legumes (Duodu & Awika, 2019;Dykes & Rooney, 2007;Liu, 2007).…”
Section: Discussionmentioning
confidence: 99%